Preschool children and their family conceptions - Dessen, Maria Auxiliadora; Ramos, Patrícia Cristina Campos (Paidéia (Ribeirão Preto), 2010)
To understand the development and diversity of the contemporary family, it is necessary to understand children's family conceptions. Thirty-three preschool children participated in the study (aged 3, 4, and 5 years old): 15 composed the Group A (both parents had a paid job), and 18 composed the Group B (only the father had a paid job). They were inquired about their conceptions of family and mentioned the following aspects: family composition, cohabitation, and the roles of provider, caregiver and socializing agent. Children included the nuclear family, extended family members, godparents, friends and pets in the composition of the family. However, the Group B emphasized the socializing function of the family more than the Group A. Moreover, children at aged 5 also provided more abstract and complex definitions than the other ones. The data indicates that children's conceptions on current family lifestyles need to be investigated in a longitudinal and cross-cultural perspective.